Dendrimers-drug delivery systems - KERİMOĞLU, OYA; UĞURLU, TİMUÇİN (AVES PRESS LTD, 2015)
Dendrimers consisting a core, branching units around the core and surface groups also named as functional group are new polymeric drug delivery systems. The variety of dendrimers are provided with functional groups. Branching units of the dendrimer provide its growth iteratively. The space in the interior of the dendrimers allows encapsulation of the active ingredient possible. In this way, the controlled release of the active ingredient can be achieved. However, being in a very branched structure and having many functional groups on the surface provide the addition of variety of molecules and active ingredient by conjugation simultaneously. Thus, targeting of active ingredients to a specific site of the body can be achieved as well as the solubility and bioavailability of the active ingredients can be increased. In this paper, the properties of dendrimers and application areas were evaluated.
Keywords: Dendrimer; drug delivery systems; targeting